Dietary glycemic index is associated with overweight and obesity in preschool children: a national cross-sectional study in Lebanon - Cynthia Egho; Fatima Al Zahraa Chokor; Krystel Ouaijan; Nahla Hwalla; Lara Nasreddine (BMC Pediatrics)
Abstract Background Although dietary glycemic index (GI) and glycemic load (GL) have been proposed to modulate overweight risk, evidence in preschoolers remains scarce and contentious, and lacking in the Eastern Mediterranean Region (EMR). This cross-sectional national survey investigated the association of dietary GI and GL with overweight/obesity in Lebanese preschoolers (n = 518; aged 2–5 years). Methods The study is based on a national cross-sectional survey conducted in 2012/2013 “Early Life Nutrition and Health, ELNAHL". Sociodemographic data were obtained using a multi-component questionnaire, and anthropometric characteristics were measured. The 24 h recall approach was used to collect dietary data. The calculations of daily dietary GI and GL were based on available carbohydrates (and repeated using total carbohydrates). Three logistic regression models were performed to investigate the association of dietary GI and GL with overweight/obesity, per unit and per 10-unit increases. Results In this study sample, 9.5% of the preschool children were found to be overweight/obese. Average dietary GI was determined at 56.1 ± 0.3 and dietary GL at 99.2 ± 1.8, when using available carbohydrates. The full regression model (model 3) which was adjusted for demographic/socioeconomic variables and energy and macronutrients’ intakes, showed a significant association between dietary GI and overweight/obesity, per unit and per 10 units increases (odds ratio (OR): 1.10; 95% confidence interval (CI): 1.09–1.11 and OR: 2.67; 95% CI: 2.45–2.92, respectively), while only a slight association was observed for GL (OR: 1.01, 95% CI: 1.00, 1.01 and OR: 1.05, 95% CI: 1.04, 1.07 for 1 unit and 10 units increases of GL, respectively). Similar results were obtained when using total carbohydrates for GI and GL calculations. Conclusions This study shows that each 10-unit increase in dietary GI was linked with approximately three-fold higher odds of overweight/obesity amongst Lebanese preschoolers, suggesting that dietary GI may be of public health significance in the epidemic of childhood overweight.